Asymmetric influence of renewable energy, ecological governance, and human development on green growth of BRICS countries. (April 2023) - Wang, Haohui; Peng, Gang; Luo, Yan; Du, Hongmei
Abstract: Due to adverse environmental consequences, green growth or environmentally adjusted multifactor productivity growth is indispensable for sustainable development. However, despite its significance, the driving factors of green growth remain underexplored in empirical evidence. Moreover, ecological governance and renewable energy consumption may direct the movement of green growth. Therefore, this study unveils the relevance of renewable energy consumption, environmental policy stringency, human development, and R&D spending in promoting or inhibiting the green growth of BRICS economies from 1990 to 2019. Using the Method of Moments Quantiles (MMQR), the findings report that renewable energy consumption, ecological governance, human development, and R&D spending stimulate green growth. The positive influence of these factors is substantial at higher quantiles of green growth. Manifestly, ecological governance significantly moderates the positive effects of renewable energy, implying that stringent environmental policies encourage higher energy transition and green growth. These findings are also echoed by alternative estimators and offer valuable policy recommendations. Highlights: MMQR applied on BRICS panel to explore drivers of green growth (GG). Renewable energy, human capital, and ecological governance stimulate GG. Ecological governance significantly moderates the positive effects of clean energy. The influence of the above drivers is more substantial at higher quantiles of GG.